2018
DOI: 10.1371/journal.pone.0205023
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive functions in Desmodus rotundus: A comparison between seasons in a morphological context

Abstract: Reproductive seasonality in Neotropical bats has been assessed to the better understand their reproductive behavior. This knowledge is especially important for the control of Desmodus rotundus population as it is a transmitter of rabies virus. Therefore, we aimed to evaluate the functional activity of testis and epididymis of D. rotundus in dry and rainy seasons under a morphological approach. We observed an increase in tubular diameter and epithelial height of the seminiferous tubules during the rainy season.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
(58 reference statements)
2
5
0
1
Order By: Relevance
“…The highest percentage of seminiferous epithelium observed in the rainy season led directly to the lowest percentage of lumen in the same season, which was similar to that observed in this species in an Atlantic forest region [28]. This indicates that the highest percentage of seminiferous epithelium observed in the rainy season is associated with a greater proliferation of germline cells in a period of greater food resources [17,29].…”
Section: Biometry and Morphometry Of Seminiferous Tubulessupporting
confidence: 80%
See 1 more Smart Citation
“…The highest percentage of seminiferous epithelium observed in the rainy season led directly to the lowest percentage of lumen in the same season, which was similar to that observed in this species in an Atlantic forest region [28]. This indicates that the highest percentage of seminiferous epithelium observed in the rainy season is associated with a greater proliferation of germline cells in a period of greater food resources [17,29].…”
Section: Biometry and Morphometry Of Seminiferous Tubulessupporting
confidence: 80%
“…The average tubular diameter presented by the animals in this study was considerably larger when compared both to that found in other bat species and when compared to that found in the same species, in the Atlantic forest. The height of the seminiferous epithelium followed the same trend [ 15 , 16 , 17 , 24 , 28 ]. In addition, while most mammals usually have an average tubular diameter ranging from 180 to 300 μm [ 30 , 31 ], the value found here (432.17 μm) is the largest value so far reported.…”
Section: Discussionmentioning
confidence: 99%
“…Authors have suggested that testosterone and other testicular factors might regulate the integrity of BEB, especially Cldn-1 expression. 7,14 A recent study reported that serum testosterone levels did not change in D. rotundus captured in both rainy and dry seasons, 26 indicating that other factors may be regulating the histological alterations observed here. In mink, low testosterone levels at the end of reproductive season did not modify BEB structure in contrast to the alterations found in its blood-testicular barrier.…”
Section: Discussionmentioning
confidence: 57%
“…Although D. rotundus bats were not evaluated monthly during rainy season by 26, this species exhibited intense activity of seminiferous epithelium in producing mature cells after the dry season that corresponds to their mating season, with consequent increase in sperm numbers in caput/corpus epididymis. 26 Thus, it is possible that lumicrine contents may differ between the rainy and dry season. Notably, the profile of luminal fluid content display substantial segmentto-segment variations, 44 and these differences may dramatically change during mating season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation